Macronutrient Analysis Of Crab Meat Analogue Made From Non-Consumable Fish With Alginate Addition - Ellya Sinurat; Singgih Wibowo; Dina Fransiska (Indonesian Journal of Pharmaceutical Science and Technology, 2017)
The crab meat analogue products using alginates and proteins such as soybean. A mixture of sh added alginate croslinking with calcium chloride making gel and water retention. The purpose of this study to analysis macronutrient from the effects of alginate addition to the characteristics of the crab meat analogue. The formulation was made from the combination of alginate from Sargassum sp. The formulation was applied to the surimi from silver giddy (Gerres Kapas Blkr) to make crab meat analogue with different concentrations (0.25%, 0.5%, 0.75%, 1%). Parameters used to study the effects were moisture content, total ash, protein content, fat content, thiobarbituric acid value and sensory evaluation. The chemical analysis, moisture content, and ash content analysis showed a signi cant difference among the treatments, while the thiobarbituric acid value showed no difference among the samples. Based on sensory evaluation, the most preferred product was formula A (0.25% alginate) in terms of texture, taste, juiciness and overall acceptance with the characteristics of 2.47% ash content, 75.98% moisture content, 0.47% fat content, 12. 07% protein content, thiobarbituric acid value of 0.69 μmol/g. Keyword : crab meat analog, alginate, macronutrient, non consumable, Sargassum sp.